2014
DOI: 10.1364/josaa.31.001408
|View full text |Cite
|
Sign up to set email alerts
|

Computational aspects of the through-focus characteristics of the human eye

Abstract: Calculating through-focus characteristics of the human eye from a single objective measurement of wavefront aberration can be accomplished through a range of methods that are inherently computationally cumbersome.A simple yet accurate and computationally efficient method is developed, which combines the philosophy of the extended Nijboer-Zernike approach with the radial basis function based approximation of the complex pupil function. The main advantage of the proposed technique is that the increase of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Moreover, asymmetric aberrations themselves significantly negatively influence retinal image quality, which could be the major reason coma or secondary astigmatic aberrations have drawn less attention. Asymmetric aberrations degrade retinal image quality for far vision, but can increase the DoF of the eye, 46 48 thus a trade-off exists between an optimal level of retinal image quality and the DoF. 28 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, asymmetric aberrations themselves significantly negatively influence retinal image quality, which could be the major reason coma or secondary astigmatic aberrations have drawn less attention. Asymmetric aberrations degrade retinal image quality for far vision, but can increase the DoF of the eye, 46 48 thus a trade-off exists between an optimal level of retinal image quality and the DoF. 28 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…In order to assess accuracy, we carried out a number of numerical experiments where we calculated U. For the ideal wavefront (Φ ≡ 0) and zero defocus ( f = 0), the results were discussed in [37], where it was shown that the two semi-analytic methods performed similarly, although GRBF calculations were done at a much lower cost.…”
Section: Accuracymentioning
confidence: 99%
“…Such class of functions allows also for an easy modeling of low and high-order oscillations. For experiments with a wavefront comprised of basically low-frequency oscillations see [37]. Here we have used the function given by…”
Section: Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…These analytical solutions include the first Lommel solution, the second Lommel solution, the Nijboer's solution with Zernike polynomials, etc. [2,4,5,9,10]. However, for a general input field, there is no analytical solution for the Fresnel transform, and it is often solved numerically [11].…”
Section: Optical Society Of Americamentioning
confidence: 99%